Genre Representation and Curriculum Alignment in English for Nusantara for Grade VII: A Critical Content Analysis of Text Types under the Merdeka Curriculum - Qomah, Isti; Zamzam, Ahmad; Arafiq, Arafiq (LITPAM, 2026)
This study critically examines the representation of text genres in English for Nusantara for Grade VII and evaluates the extent to which the textbook supports the genre-based literacy expectations of the Merdeka Curriculum. The study responds to the need for systematic textbook evaluation because textbooks remain central instructional resources in English as a foreign language classrooms and because curriculum alignment cannot be inferred merely from official textbook status. A qualitative content analysis was employed to identify, classify, and interpret the main reading texts in the textbook by using three genre indicators: social function, generic structure, and linguistic features. The analysis shows that the textbook represents four principal genres, namely descriptive, procedure, recount, and report texts. Descriptive texts dominate the textbook and appear across several chapters, whereas procedure, recount, and report texts occur more narrowly and receive less sustained pedagogical attention. This pattern indicates partial alignment with Phase D learning outcomes, especially because students are expected to read, view, evaluate, and produce different kinds of texts in print, digital, visual, multimodal, and interactive forms. However, the uneven distribution also suggests that students may receive stronger support for describing familiar people, places, and objects than for developing informational, chronological, procedural, and analytical literacy. The novelty of this study lies in conceptualizing genre distribution as a critical indicator of curriculum alignment rather than treating alignment as the simple presence of selected text types. The study recommends that teachers supplement the textbook with additional model texts and genre-based tasks so that students can experience broader communicative purposes and more balanced literacy development.